2020
DOI: 10.3390/molecules25163717
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Access to π-Conjugated Molecular Materials via Direct (Hetero)Arylation Reactions in Water and under Air

Abstract: Direct (hetero)arylation (DHA) is playing a key role in improving the efficiency and atom economy of C–C cross coupling reactions, so has impacts in pharmaceutical and materials chemistry. Current research focuses on further improving the generality, efficiency and selectivity of the method through careful tuning of the reaction conditions and the catalytic system. Comparatively fewer studies are dedicated to the replacement of the high-boiling-point organic solvents dominating the field and affecting the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…As we could expect, recurring to flash chromatography caused a significant increase of E -factors, with values ranging between 351 and 4279 ( 5b , d , k ). However, all our values look similar to others calculated according to the same principles. , …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…As we could expect, recurring to flash chromatography caused a significant increase of E -factors, with values ranging between 351 and 4279 ( 5b , d , k ). However, all our values look similar to others calculated according to the same principles. , …”
Section: Resultssupporting
confidence: 88%
“…However, all our values look similar to others calculated according to the same principles. 77,82 Eco-scale values ranged from 41 to 81: according to the original paper by Van Aken et al, 66 the reaction conditions in DESs can thus be ranked as "excellent" (Eco-scale >75) for the preparation of compounds 5c,e,g,i, and "acceptable" (Eco-scale >50) for compounds 5a,b,f,h,j. Therefore, "inadequate" (Ecoscale <50) values were obtained only for the preparation of 5d,k, mostly due to the lower isolated yields of those compounds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Beverina et al reported a representative example of sustainable direct C-H bond ortho-arylation of octafluorobiphenyl with an aryl bromide, performed in Kolliphor 2% in H 2 O/ toluene (9 : 1 v/v) mixture. 131 One of the most appealing features of the protocol is definitely the application of a micellar catalysis: the use of Kolliphor, which is an FDA-approved surfactant obtained by the reaction of castor oil with ethylene oxide, allowed for the development of micellar catalytic systems within which direct arylation reactions may occur. The key concept of micellar catalysis is related to the preferential accumulation of organic compounds within the lipophilic pockets formed by the self-assembly of surfactants in H 2 O.…”
Section: Direct C-h Bond Arylation Of (Hetero)arenes In Watermentioning
confidence: 99%
“…Beverina and co-workers reported an extensive investigation of sustainable direct C-H bond arylation reactions of 2-(nhexyl)thiophene, 2,2′-bithiophene, 3,4-ethylenedioxythiophene and thieno[3,4-c]pyrrole-4,6-dione with aryl bromides, performed in Kolliphor 2% in H 2 O/toluene (9 : 1 v/v) mixture. 131 The use of Kolliphor allowed for the application of a micellar catalysis approach: direct C-H arylation reactions occurred within the lipophilic pockets of micelles, where thanks to the high concentration and local polarity effects, reactions are very efficient. In addition to the use of a micellar catalysis, the overall sustainability of the process was further confirmed by E-factors (i.e., the mass ratio between organic wastes and product) in all cases in the order of 10 2 (between 179 and 556), which are low values, considering that they also include purification.…”
Section: Direct C-h Bond Arylation Of (Hetero)arenes In Watermentioning
confidence: 99%
See 1 more Smart Citation